Bulk and surface investigation of Porous Silicon Nanostructure (PSN) / Mohd Ridhuan Ismail - Ismail, Mohd Ridhuan (2006)
In this project, the bulk and surface studies of porous silicon nanostructure were carried out by ellipsometry and photoluminescence spectroscopy (PL) in visible region. The spectra of visible luminescence, dependences of refractive index of PS surface layers on porosity were investigated. Investigations on bulk properties of porous silicon (PS) were done by ellipsometry using an ellipsometer with the light source (He-Ne laser) of wavelength 632.8 nm. Less porosity of PS samples correspond to higher refractive index of the surface region. This refractive index is compatible with the He-Ne laser wavelength. Investigations on surface properties of PS were done using photoluminescence spectrometer of 380 nm Xe light source. The PS surface was found to emit visible luminescence at the room temperature. This was the significance that cannot be found in the bulk silicon. The increase and decrease of PL intensity, PL peak position and full width at half maximum (FWHM) in presence of externally applied lateral current is due to the tunneling of electrons from neighboring quantum well to the holes taking part in the radiative combination and supports the assumption of quantum confinement of holes as the origin of PL in porous silicon.